Coordinated Access and Coordinated Entry System Processes in the Housing and Homelessness Sector: A Critical Commentary on Current Practices. Issue 6 (2nd November 2022) - Ecker, John; Brown, Molly; Aubry, Tim; Pridham, Katherine Francombe; Hwang, Stephen W.
Abstract: Coordinated access and coordinated entry systems have become central features in community responses to homelessness in Canada and the United States. Coordinated systems assess individuals and families experiencing homelessness on their needs, prioritize them based upon these needs, and then match them to appropriate housing. Despite the widespread implementation of coordinated systems, there have been few evaluations of the effectiveness of these systems. The current article fills this knowledge gap by providing an overview of the evidence and a critical commentary on the four pillars of coordinated systems—(a) access, (b) assessment, (c) prioritization, and (d) matching and referral—and presenting a critique of current practices. Using the policy streams framework, the critique demonstrates that the components of coordinated systems lack a strong evidence base and that there is little evidence that coordinated systems improve individual-level outcomes such as length of stay in housing. Further, current coordinated system practices, particularly assessments, may be contributing to inequitable access to housing. Limitations of the critique and considerations for implementation are discussed.